2021
DOI: 10.1002/lt.26094
|View full text |Cite
|
Sign up to set email alerts
|

Post–Liver Transplant Acute Kidney Injury

Abstract: Acute kidney injury (AKI) is a common condition following liver transplantation (LT). It negatively impacts patient outcomes by increasingthe chances of developing chronic kidney disease and reducing graft and patient survival rates. Multiple definitions of AKI have been proposed and used throughout the years, with the International Club of Ascites definition being the most widely now used for patients with cirrhosis. Multiple factors are associated with the development of post-LT AKI and can be categorized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 97 publications
0
32
0
1
Order By: Relevance
“…9 These patterns of microbiota disruption characterized by dominance of a single taxa and loss of diversity were significant predictors of mortality in allogeneic hematopoietic-cell transplantation. 26 Furthermore, gut dysbiosis may 29 In our cohort, VRE colonization was associated with higher pretransplant levels of creatinine (and MELD scores) that may explain in part the higher risk of AKI posttransplant. VRE colonization-associated dysbiosis may also contribute to the increased risk of AKI.…”
Section: Discussionmentioning
confidence: 80%
“…9 These patterns of microbiota disruption characterized by dominance of a single taxa and loss of diversity were significant predictors of mortality in allogeneic hematopoietic-cell transplantation. 26 Furthermore, gut dysbiosis may 29 In our cohort, VRE colonization was associated with higher pretransplant levels of creatinine (and MELD scores) that may explain in part the higher risk of AKI posttransplant. VRE colonization-associated dysbiosis may also contribute to the increased risk of AKI.…”
Section: Discussionmentioning
confidence: 80%
“…For example, Dong and colleagues identified several preoperative risk factors for developing AKI after LT, including high BMI, preexisting hypertension, type 2 diabetes, reduced donor liver quality, and hepatorenal syndrome. 55 Preoperative risk factors for developing EAD 27,47 and biliary complications 32,56,57 after LT have also been identified in the literature. Transplant centers should consider monitoring patients with these comorbidities closely and apply appropriate interventions to prevent the AKI, biliary complications, and EAD from occurring whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…58 Poor donor allograft quality and interoperative factors may also increase a recipient's chances of developing AKI. 55 Calcineurin inhibitors (CNIs) used for immunosuppression after transplant are known to be nephrotoxic, and they may contribute to AKI after LT. Immunosuppression protocols that delay the use of CNIs have been shown to protect kidney function. 51 However, a recent twocenter study by Ciria and colleagues suggested that lower-dose use of the CNI tacrolimus had no affect the development of AKI and may not significantly impact post-LT renal function in patients with normal preoperative renal function.…”
Section: Acute Kidney Injury (Aki)mentioning
confidence: 99%
See 1 more Smart Citation
“…Tacrolimus is metabolized by the cytochrome P450 3A4 enzyme system, and many drugs can induce or inhibit this enzyme, affecting its levels. It can cause serious side effects such as AKI and is a hazard that deserves our attention, although there hasn't been much research [92] . Interestingly, some glucocorticoid drugs may cause kidney damage in the anti-inflammatory treatment of COVID-19 and in the rescue of critically ill patients [93] , [94] .…”
Section: Patients With Covid-19 and Secondary Nephropathymentioning
confidence: 99%